If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -4y = 2x + -4 Reorder the terms: -2x + -4y = -4 + 2x Solving -2x + -4y = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x + -4y = -4 + 2x + -2x Combine like terms: -2x + -2x = -4x -4x + -4y = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -4x + -4y = -4 + 0 -4x + -4y = -4 Add '4y' to each side of the equation. -4x + -4y + 4y = -4 + 4y Combine like terms: -4y + 4y = 0 -4x + 0 = -4 + 4y -4x = -4 + 4y Divide each side by '-4'. x = 1 + -1y Simplifying x = 1 + -1y
| -8=-2x-6 | | -98+x=56-10x | | -17-37=26 | | 15-7=x | | 2x-14=x-7 | | 6y+5x=-3 | | -2x+5x^2-7=0 | | -4=t+8 | | -5+33=7 | | -7r-8=14 | | -5+48=7 | | 3(y-9)4=-2y | | 4z-43=2z+80 | | 4(2z-8)-(z-9)=8(8-7z) | | -5+36=7 | | -5g+1.2=-18.8 | | 10x-186=90-2x | | 7(k+9)=9(k-5)-14 | | 3y=4(x+6) | | -(5x+8)+12=17+17 | | 4f+2= | | -7j+62=-2g+12 | | 11b^2-71b-42=0 | | 5-c-10-5c-2=8 | | M=-4m+15 | | -4x-6x=20 | | Y=-1x+5 | | 8x+x-5=40 | | .4x+.4=g | | 1.4x-3.5=0.6x-2.54 | | 4+7f=f+16 | | 1+5x=7+3x |